Innovative Drug Modalities for the Treatment of Advanced Prostate Cancer - Maurizio Capuozzo; Mariachiara Santorsola; Monica Ianniello; Francesco Ferrara; Andrea Zovi; Nadia Petrillo; Rosa Castiello; Maria Rosaria Fantuz; Alessandro Ottaiano; Giovanni Savarese (Diseases)
Prostate cancer, a prevalent malignancy affecting the prostate gland, is a significant global health concern. Androgen-deprivation therapy (ADT) has proven effective in controlling advanced disease, with over 50% of patients surviving at the 10-year mark. However, a diverse spectrum of responses exists, and resistance to ADT may emerge over time. This underscores the need to explore innovative treatment strategies for effectively managing prostate cancer progression. Ongoing research endeavors persist in unraveling the complexity of prostate cancer and fostering the development of biologic and innovative approaches, including immunotherapies and targeted therapies. This review aims to provide a valuable synthesis of the dynamic landscape of emerging drug modalities in this context. Interestingly, the complexities posed by prostate cancer not only present a formidable challenge but also serve as a model and an opportunity for translational research and innovative therapies in the field of oncology.